Modeling Emotion Regulation and Subjective Happiness: Smartphone Addiction as a Mediator - Satici, Begum; Deniz, M. Engin (TURKISH GREEN CRESCENT SOC, 2020)
This study aimed to investigate the mediational role of smartphone addiction in the relationship between emotion regulation and subjective happiness. Participants were 320 university student volunteers (167 women and 153 men) from two state universities in Turkey. They completed a self-report questionnaire about emotion regulation, smartphone addiction, and subjective happiness. Structural equation modeling (SEM) and bootstrapping were applied to test the mediational role of smartphone addiction in the relationship between emotion regulation and subjective happiness. The results indicated that reappraisal predicted lower smartphone addiction scores and higher subjective happiness scores. On the contrary, suppression predicted higher smartphone addiction scores and lower subjective happiness scores. In addition, smartphone addiction proved to be a partial mediator between emotion regulation strategies and subjective happiness. Therefore, the results of this study support the evidence for the impact of emotion regulation on subjective happiness through smartphone addiction.
Keywords: Smartphone addiction; emotion regulation; subjective happiness; structural equation modelling; bootstrapping; INDIVIDUAL-DIFFERENCES; PERSONALITY; RELIABILITY; DEPRESSION; ANXIETY; Substance Abuse